Spiritual Intelligence and its Relationship to Gender and Achievement Level of Students in The Faculty of Education at Yarmouk University in Jordan - El- Rabeea, Faisal (Jordan Journal of Educational Sciences, 2013)
among Yarmouk University students, and whether this level varies according to students gender and level of achievement. It also aimed at determining the possibility of predicting academic achievement from the components of Spiritual Intelligence. The sample consisted of (256) students selected from the Faculty of Education at Yarmouk University. The study results showed that the level of Spiritual Intelligence was medium, with no significant differences in the level of Spiritual Intelligence or any of its dimensions due to the sex factor. Significant differences were found in the level of Spiritual Intelligence and the dimensions of Critical Existential Thinking, Personal Meaning Production, Transcendental Awareness due to achievement level in favor of the high achievement level. The results also showed that Critical Existential Thinking, Personal Meaning Production, and Transcendental Awareness domains can predict academic achievement